Effect of salt water intrusion on the groundwater resources at Delta of wadi Kiraf area, Shaltein, Egypt - ABD ALLA, Mohamed A. (Contributions to Geophysics and Geodesy, 2021)
The hydrogeophyscial investigation plays a very important role in the assessment of groundwater in the Delta wadi Kiraf area. This area is located at the triangle Halaib-Shalatin area, Southeastern corner of Egypt. The present work was selected to show the drawbacks of the effects of saltwater intrusion on the groundwater potentiality using the vertical electrical sounding technique. Many conduit faults with different orientations are presented at or near to polluted sites. Thirty vertical electrical sounding stations (VES) were conducted in the concerned area. The Schlumberger configuration was used with distances of current electrodes that varied from 1.5 m up to 600 m. The correlation of the deduced geoelectric parameters and the available geological information was helpful in establishing the specific resistivities of the formations. The interpretation of the acquired resistivity field data led to the classification of the geoelectrical and geological successions to four geoelectric units; the first unit divided into two units corresponding to surface layer (first unit corresponding to wadi deposits and the second unit corresponding to high resistivity due to weathering materials), while the second unit is a sandstone layer saturated with fresh/brackish water, and the third geoelectrical unit has resistivity values less than one Ωm which reflects the existence of saltwater. The fourth geoelectrical unit: This layer represents the basement rocks (metamorphic rocks) and it appeared at VES’s 41, 42, 43, 44 and 45. Its true resistivity values range between 25.2 and 5500 Ωm. It represents dry to saturated fractured basement rocks. Generally, resistivity values decrease with depth with the highest values of the unsaturated zone near the surface to the lowest values of saltwater saturated zone. The resultant models from resistivity measurements agree with other lithologic data. Also, The Least Squares ABIC technique was applied to the same data set.